Ground State of Hydrogen

Compute the radial wavefunction of an electron in the ground state of hydrogen.

Note : recall that ρ = r m e 2 4 π ϵ 0 2 n \rho = \dfrac{rme^2}{4\pi \epsilon_0 \hbar^2 n} for n n the energy level of the electron.

( ρ 2 r ) 3 / 2 e ρ \left(\frac{\rho}{2r}\right)^{3/2} e^{-\rho} ( ρ r ) 1 / 2 e 2 ρ \left(\frac{\rho}{r}\right)^{1/2} e^{-2\rho} 1 2 ( ρ r ) 3 / 2 e ρ / 2 \frac12 \left(\frac{\rho}{r}\right)^{3/2} e^{-\rho/2} 2 ( ρ r ) 3 / 2 e ρ 2\left(\frac{\rho}{r}\right)^{3/2} e^{-\rho}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Matt DeCross
May 10, 2016

Relevant wiki: Hydrogen Atom

The ground state of hydrogen corresponds to n = 1 n=1 , = 0 \ell = 0 . The radial solutions as given in the relevant wiki are:

R n ( r ) = 1 r ρ + 1 e ρ v ( ρ ) . R_{n \ell} (r) = \frac{1}{r} \rho^{\ell + 1} e^{-\rho} v(\rho).

Plugging in these values of n n and \ell gives:

R 10 ( r ) = 1 r ρ e ρ v ( ρ ) . R_{10} (r) = \frac{1}{r} \rho e^{-\rho} v(\rho).

The function v ( ρ ) v(\rho) is defined by the series:

v ( ρ ) = j = 0 c j ρ j , c j + 1 = 2 ( j + + 1 n ) ( j + 1 ) ( j + 2 + 2 ) c j . v(\rho) = \sum_{j=0}^{\infty} c_j \rho^j, \qquad c_{j+1} = \frac{2(j+ \ell + 1 - n)}{(j+1)(j + 2\ell + 2)} c_j.

All c j c_j are zero after j max = n 1 j_{\text{max}} = n-\ell - 1 . In this case, all c j c_j are thus zero after c 0 c_0 , so v ( ρ ) = 1 v(\rho) = 1 up to normalization, and

R 10 ( r ) = 1 r ρ e ρ . R_{10} (r) = \frac{1}{r} \rho e^{-\rho}.

Normalizing, should have:

0 C 2 ( 1 r ρ e ρ ) 2 r 2 d r = 1 C 2 4 r ρ = 1 C = 2 ρ r . \int_0^{\infty} C^2 (\frac{1}{r} \rho e^{-\rho})^2 r^2 dr = 1 \implies \frac{C^2}{4} \frac{r}{\rho} = 1 \implies C = 2\sqrt{\frac{\rho}{r}}.

Therefore, the solution is given by:

R 10 ( r ) = 2 ρ r ρ r e ρ , R_{10} (r) =2\sqrt{\frac{\rho}{r}} \frac{\rho}{r} e^{-\rho},

which is equivalent to the listed answer.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...